Epidemiological changes and molecular characteristics of Brucella strains in Ningxia, China - Liu, Guangtian; Ma, Xueping; Zhang, Ruiqing; Lü, Jufen; Zhou, Pan; Liu, Bofei; Liu, Tao; Ren, Hui; Liu, Zhiguo; Li, Zhenjun; Jiang, Xuefeng (Frontiers in Microbiology, 2024)
Objective Human brucellosis causes serious public health concerns in Ningxia, China.Methods This study employed epidemiological, bacteriological, and multiple-locus variable-number tandem repeat analysis (MLVA) methods to conduct an epidemiological investigation, which is necessary for devising tailored control strategies. Results Between 1958 and 2022, 29,892 cases were reported, with an average annual number of cases and incidence of 467 and 7.1/100,000, respectively.The epidemic situation gradually worsened, with cases escalating from 26 cases in 2005 to 6,292 in 2022, with the incidence rate rising from 0.441 in 2005 to 86.83 in 2022.Geographically, the disease spread from a single affected county in 2004 to encompass all 22 counties in 2022. Yanchi County had the highest incidence, followed by the Hongsibao and Tongxin counties. These data suggest that Brucella infection has become a rampant regional concern in human brucellosis. Between 1958 and 2019, a total of 230 Brucella strains were identified across four studied hosts. These strains comprised four species with 12 biovars, including B. melitensis bv. 1, bv. 2, bv. 3, B. abortus bv. 1, bv. 3, bv. 4, bv. 5, bv. 6, bv. 7, B. suis bv. 1 and bv. 3, and B. canis. These data highlight the high species/biovars and host diversity of the Brucella population, posing a substantial challenge to brucellosis surveillance. There was an apparent transition from multiple species/biovars historically to the current dominance of a single species, B. melitensis, emphasizing the requirement for strengthening surveillance of B. melitensis. Genotypes 42 and 116, constituting 96.2% of the total number of genotypes, predominated in panel 1 and MLVA-11, indicating that all strains belong to the East Mediterranean lineage. MLVA cluster analysis revealed persistent transmission of dominant circulating genotypes, presenting an epidemic pattern characterized primarily by epidemiologically related cases with a few sporadic cases.Strains in this study exhibited high genetic homogeneity with strains from the Northwest, and those from Kazakhstan and Mongolia.Conclusion The epidemic situation of human brucellosis has gradually worsened; the rampant epidemic of the disease has become a regional concern. The present study highlights that implementing the of targeted surveillance and intervention strategies is urge.